Navigating Digital Disruptions: Internalizing Pancasila Values in Islamic Primary School Character Education - Yualita, Putri Nur Wahidah; Rahmawati Tri Utami; Icha Dwi Febriana; Isna Fatimatuz Zahroh (Journal of Smart Pedagogy and Education, 2025)
The rapid digitalization of education creates a "digital paradox," where hyper-connectivity catalyzes socio-emotional crises and ethical degradation among primary learners. This study investigates the multi-dimensional integration of Pancasila values within Islamic primary Social Studies, addressing the critical research gap regarding the practical value internalization under digital saturation. Employing a qualitative single-case study at SDI Al-Alifah Palembang, researchers utilized observations, interviews, and documentation. Findings indicate that while school-based cultural habituation effectively constructs a "theocentric civic identity," these values remain vulnerable to unmoderated domestic digital exposure and parental time scarcity. The research concludes that sole institutional effort is insufficient; a robust collaborative framework linking schools, families, and community networks is essential. We propose integrating culturally responsive "smart pedagogies" to sustain character development, ensuring that digital natives retain an ethical compass to navigate the multifaceted complexities of contemporary globalized society and the digital era.